Analysis of Natural Science Problem Solving Ability at Junior High School on Temperature and Heat Material - Arrayan, Hamdi; Suprapto, Nadi; Munasir, M; Ilhami, Fasih Bintang; Sihombing, Rizky Agassy (Studies in Learning and Teaching, 2025)
This research aims to examine junior high school students' problem-solving abilities on the topic of temperature and heat. A qualitative descriptive method was employed, involving 20 seventh-grade students from SMP Negeri 1 Ngoro during the 2024/2025 academic year. The instrument used was an essay test, with problem-solving indicators based on Polya’s stages: understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. The findings revealed that students’ performance across these four stages remained relatively low. Most students tended to bypass crucial steps and proceeded directly to the solution without proper planning. Only a few were able to follow the entire process coherently and accurately. These results are consistent with previous studies, highlighting that students’ problem-solving skills vary significantly depending on their ability level. Therefore, more contextual, interactive, and student-centered learning strategies are necessary to enhance critical and scientific thinking skills in problem-solving.